Treatment of Cirrhosis-Associated Hyponatremia with Midodrine and Octreotide - Patel, Sharad; Nguyen, Dai-Scott; Rastogi, Anjay; Nguyen, Minh-Kevin; Nguyen, Minhtri K. (Frontiers in Medicine, 2017)
Background Hyponatremia in the setting of cirrhosis is a common electrolyte disorder with few therapeutic options. The free water retention is due to non-osmotic vasopressin secretion resulting from the cirrhosis-associated splanchnic vasodilatation. Therefore, vasoconstrictive therapy may correct this electrolyte abnormality. The aim of this study was to assess the efficacy of midodrine and octreotide as a therapeutic approach to increasing urinary electrolyte free water clearance (EFWC) in the correction of cirrhosis-associated hyponatremia. Methods This observational study consisted of 10 patients with cirrhosis-associated hyponatremia. Hypovolemia was ruled out as the cause of the hyponatremia with a 48-hour albumin challenge (25 gm IV q6 hrs). Patients whose hyponatremia failed to improve with albumin challenge were started on midodrine and octreotide at 10 mg po tid and 100 mcg sq tid respectively, with rapid up-titration as tolerated to respective maximal doses of 15 mg tid and 200 mcg tid within the first 24 hours. We assessed urinary electrolyte-free water clearance (EFWC) and serum sodium concentration before and 72 hours after treatment. Results Pre-treatment serum sodium levels ranged from 119 mmol/L to 133 mmol/L. The mean pre-treatment serum sodium concentration ± SEM was 124 mmol/L ± 1.6 vs. 130 mmol/L ± 1.5 post treatment (p = 0.00001). The mean pre-treatment urinary EFWC ± SEM was 0.33 L ± 0.07 vs 0.82 L ± 0.11 post treatment (p = 0.0003). Conclusion Our data shows a statistically significant increase in serum sodium concentration and urinary EFWC with the use of midodrine and octreotide in the treatment of cirrhosis-associated hyponatremia.